STRATEGI COMMUNITY-BASED MARKETING TOKO BUKU WARUNG SASTRA YOGYAKARTA DALAM MEMBENTUK BRAND LOYALTY - Bintang, Hafidz; Oni Dwi Arianto (Universitas Negeri Surabaya, 2025)
This study analyzes the community-based marketing strategy implemented by Warung Sastra Bookstore Yogyakarta in building brand loyalty. Using a qualitative descriptive approach, data were collected through in-depth interviews and observations and analyzed based on Juárez’s (2011) community-based marketing theory. The findings reveal that Warung Sastra adapts the eight elements of the theory into three main categories: core elements, programmatic elements, and external elements, tailoring its strategy to the needs of its community and customers. This strategy contributes to the development of brand loyalty, which is divided into two aspects: attitudinal loyalty—customers’ emotional attachment and perception of the community’s value—and behavioral loyalty—reflected in their consistent engagement and transactions. Unlike the original theory, Warung Sastra does not explicitly construct a community identity but allows it to develop organically. These findings affirm that community-based marketing not only fosters brand loyalty but also strengthens the literacy ecosystem. This study has theoretical and practical implications, particularly for the literacy industry and social impact-driven sectors in understanding the effectiveness of community marketing strategies in building sustainable customer loyalty. Keywords: Community-Based Marketing, Brand Loyalty, Warung Sastra, Literacy